2003
DOI: 10.2174/1381612033454324
|View full text |Cite
|
Sign up to set email alerts
|

Immune Abnormalities and Endotoxemia in Patients with Ulcerative Colitis and in Their First Degree Relatives: Attempts at Neutralizing Endotoxin- Mediated Effects

Abstract: Proinflammatory cytokines released from monocytes/macrophages, in particular tumor necrosis factor (TNF)-alpha, interleukin (IL)-1, IL-6, and IL-8 seem to play an important role in Inflammatory Bowel Disease (ulcerative colitis and Crohn's disease). Endotoxins or lipopolysaccharides, derived from the outer membrane of Gram-negative bacteria interact with CD14 on surface membrane of macrophages, thus triggering a signal cascade, which leads to the production and release of proinflammatory cytokines, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…This observation provides further support to the notion that the inflammation persisted in the combined treatment group regardless of continued or discontinued injections. Once again, these findings are in line with the findings of chronic UC in humans [35,36] . Further characterization of our animal model was carried out at the molecular level in order to evaluate the expression of inflammatory signaling.…”
Section: Tnf-α Protein Expressionsupporting
confidence: 90%
See 1 more Smart Citation
“…This observation provides further support to the notion that the inflammation persisted in the combined treatment group regardless of continued or discontinued injections. Once again, these findings are in line with the findings of chronic UC in humans [35,36] . Further characterization of our animal model was carried out at the molecular level in order to evaluate the expression of inflammatory signaling.…”
Section: Tnf-α Protein Expressionsupporting
confidence: 90%
“…These changes were less pronounced in the iodoacetamide groups and were minimal or absent in the B-treated and MC-treated control groups (Figure 4). Therefore, changes in the microscopic structure of the combined treatment subgroups mimicked the changes commonly encountered in severe UC in humans [30,35,36] . These include extensive hyperemia and loss of epithelial lining, ulceration of the mucosa, severe depletion of goblet cells, loss of crypts, crypt abscesses, cryptitis, with dense inflammatory cell infiltration, severe dilatation of several blood vessels, loss or thinning of muscularis mucosa, and invasion by lymphoid cells [3,17,19] .…”
Section: Tnf-α Protein Expressionmentioning
confidence: 77%
“…Bacterial lipopolysaccharide (LPS) is found in plasma of IBD patients (4) and acts, via tolllike receptor 4 activation, as an important trigger of myeloid cells that drive the Th1-type intestinal inflammatory process (5). Experimental studies have shown that LPS causes delayed gastric emptying (6,7), intestinal dysmotility (7,8) and sphincteric dysfunction (9), thus unravelling its interaction with enteric nerves.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 In ulcerative colitis (UC), damaged intestinal mucosa facilitates the influx of LPS or bacterial gut translocation, resulting in activation or worsening of intestinal inflammation. [23][24][25] Additionally, circulating levels of LPS have been documented in patients with UC, 23,24 with increased local activity of intestinal AP also occurring in these patients, 18 while locally available intestinal AP has been shown to protect mice intestinal tissue from inflammatory injury in a chronic colitis model. 26,27 The aim of the present open-label exploratory trial was to assess the safety and preliminary efficacy of exogenous intestinal AP enzyme administered intraduodenally to patients with UC and thus provide a basis for future studies of AP as a potential biologic approach in the treatment of inflammatory bowel disease (IBD).…”
mentioning
confidence: 99%